2007
DOI: 10.1038/sj.jcbfm.9600462
|View full text |Cite
|
Sign up to set email alerts
|

Aging Effects on Cerebral Blood and Cerebrospinal Fluid Flows

Abstract: Phase-contrast magnetic resonance imaging (PC-MRI) is a noninvasive reliable technique, which enables quantification of cerebrospinal fluid (CSF) and total cerebral blood flows (tCBF). Although it is used to study hydrodynamic cerebral disorders in the elderly group (hydrocephalus), there is no published evaluation of aging effects on both tCBF and CSF flows, and on their mechanical coupling. Nineteen young (mean age 27+/-4 years) and 12 elderly (71+/-9 years) healthy volunteers underwent cerebral MRI using 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
173
6
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(209 citation statements)
references
References 37 publications
18
173
6
5
Order By: Relevance
“…Importantly, the current data are consistent with others that have reported agerelated differences in MCA V mean (Buijs et al 1998;Ainslie et al 2008), and the progressive decline in CBF from the age of 30 to 70 years has been confirmed repeatedly using a variety of imaging techniques (Kashimada et al 1994(Kashimada et al , 1995Buijs et al 1998;Scheel et al 2000;Beason-Held et al 2007;Stoquart-ElSankari et al 2007). …”
Section: Methodological Considerationssupporting
confidence: 91%
“…Importantly, the current data are consistent with others that have reported agerelated differences in MCA V mean (Buijs et al 1998;Ainslie et al 2008), and the progressive decline in CBF from the age of 30 to 70 years has been confirmed repeatedly using a variety of imaging techniques (Kashimada et al 1994(Kashimada et al , 1995Buijs et al 1998;Scheel et al 2000;Beason-Held et al 2007;Stoquart-ElSankari et al 2007). …”
Section: Methodological Considerationssupporting
confidence: 91%
“…Data were analyzed by using an in-house image-processing software, 11 with an optimized CSF and blood-flow segmentation algorithm, which automatically extracts the region of interest at each level and calculates its flow curves over the 16 segments of the CC (for more details, refer to the description of the processing protocol in previous studies 11,21 ).…”
Section: Discussionmentioning
confidence: 99%
“…36 Given that our results, in particular the mean blood flow in the aHT-subjects at the extra-and intracranial levels -were similar to the elderly population studied by Stoquart-El Sankari et al in 2007 34 but different from the aHT+ population, suggests the impact of hypertension on vascular blood flow. A study by Kuyumcu et al showed conflicting results.…”
Section: Aht-vs Aht+mentioning
confidence: 87%
“…The mean cerebral blood flow in the young and elderly subjects was 688 ± 115 ml/min and 509 ± 103 ml/ min, respectively. 34 In our aHT-population, consisting of 9 patients, the mean cerebral blood flow was 508 ± 94 ml/min at extracranial level and 509 ± 103 ml/ min at intracranial level. The mean age of our aHT-population was 79 ± 5 years old, which is older than the population in the study of Stoquart-El Sankari.…”
Section: Discussionmentioning
confidence: 99%